1992
DOI: 10.1093/milmed/157.10.542
|View full text |Cite
|
Sign up to set email alerts
|

Soldiers' Dental Complaints Compared with Clinical Findings in the Military Hospital in Bologna, Italy

Abstract: There is no previous data published on the frequency and reasons for dental emergencies in the Italian Army. In this study, all the 329 soldiers who sought dental help during a 5-month period in the Military Hospital in Bologna were investigated. Prior to clinical examination, the soldiers filled out a questionnaire concerning their subjective perception about their dental treatment needs. Data from the questionnaire were then compared with the actual status findings. The results showed that endodontic problem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Few data are available: only 2 papers describe caries in the Military Forces in Italy [Calderara et al, 1992;Senna et al, 2005]; thus it is difficult to compare their results to those from the present survey. Furthermore, the second paper [Senna et al, 2005] reports oral status in a young adult population, describing quite high a caries experience.…”
Section: Discussionmentioning
confidence: 87%
“…Few data are available: only 2 papers describe caries in the Military Forces in Italy [Calderara et al, 1992;Senna et al, 2005]; thus it is difficult to compare their results to those from the present survey. Furthermore, the second paper [Senna et al, 2005] reports oral status in a young adult population, describing quite high a caries experience.…”
Section: Discussionmentioning
confidence: 87%
“…A Greek study (2) of an emergency dental center found that 35% presented with pulpitis and 7% with cellulitis. An Italian study (3) conducted in a military hospital found that 37.1% of their dental emergencies were of a pulpal origin.…”
mentioning
confidence: 99%